Experiencing the Outdoors: Enhancing Strategies for Wellbeing - Robertson, Margaret (Springer, 2016)
The space is outdoors. The experience is personal and the journey can be solitary or take place in groups. Informal or formal the places visited are sites of learning. Locked in memory our experiences in the outdoors are a constant source of wonderment and food to replenish our sense of wellbeing. Our experiences in the outdoors can endure in the abstract as ideas for developing a sense of a well lived life. They can also draw us back to places and reenergise the body. Physical and emotional wellbeing collides in the unexpected events that flourish in the outdoors. Our readiness for enjoyment and personal development are subjective states which this book challenges. Traversing the landscape of the outdoors the collection of chapters contained range from the theoretical to the practical including strategies for teaching and learning that are transdisciplinary. With ideas for practitioners as well as thoughtful reading for readers of diverse ages and interests this book includes contributions from Australia, New Zealand, Hong Kong, United Kingdom and Canada.